Kompensasi, Lingkungan Kerja, dan Motivasi Terhadap Kinerja Pegawai PT Sido Muncul - Muchamad Azis; Euis Soliha (Jurnal Ilmiah Aset, 2023)
This research aims to analyze the influence of compensation and work environment to employee performance with work motivation as moderation variable study on PT Sido Muncul Tbk. Data in this research was obtained through questionnaires distributed to 105 employees. Data analysis technique used in this research is multiple linear regression test. The result of this research proves that there is no relationship between compensation and employee performance. But on the other hand, there is a positive relationship between work environment and employee performance and the existence of work motivation affects both the relationship of compensation and work environment on employees of PT Sido Muncul Tbk.